THE IMPORTANCE OF STRESS MANAGEMENT AND MENTAL HEALTH AMONG ADULTS IN PRIMARY SCHOOL - Adhamova Mohlaroy Nodirbek qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Annotation. This article discusses the importance of stress management and mental health at the primary school level among adults. It pinpoints the main stress factors that affect teachers and other staff and describes how these would eventually impact their professional performance. This paper is going to contend that effective coping strategies and institutional support are crucial in an attempt to enhance adults’ well-being and create a healthier, more productive learning environment for students.